Exploring the role of norms and habit in explaining pro-environmental behavior intentions in situations of use robots and AI agents as providers in tourism sector - Sarmento; E. M.; Loureiro, S. M. C. (Sustainability, 2021)
In a pandemic situation, with climate change around the world, studies analyzing changes in travel patterns are welcome. This study combines three theories to propose a model on proenvironmental behavior intentions, namely, the theory of planned behavior, value–belief–norm theory and habit theory. This study aims to examine the role of social norms, personal norms and habit strength to explain pro-environmental behavior intentions. The authors collected 316 usable questionnaires from tourists in the well-known touristic Belem location in Lisbon. Personal norms were revealed to have the strongest association with pro-environmental behavior intentions, followed by habit strength. The study also identified different broad challenges to encouraging sustainable behaviors and use these to develop novel theoretical propositions and directions for future research. Finally, the authors outlined how practitioners aiming to encourage sustainable consumer behaviors can use this framework to achieve better results.